SAT0284 A Self-Administered Questionnaire May Allow General Practitioners to Perform a Rapid Screening to Identify Patients at Risk for Fragility Fractures and to Address Them to Bone Metabolism Specialized Clinical Centers. (9th June 2015) - Lumetti, F.; Fila, E.; Rossi, E.; Buffa, A.; Bortoluzzi, A.; Cagnoni, C.; Falchetti, A.; Bonaccorsi, G.; Malavolta, N.; Mascia, M.T.
Abstract : Background: The number of osteoporotic fractures is worldwide increasing and it is necessary to identify people at high risk to start effective treatment combined with a reasonable cost/benefit ratio.Since the majority of fragility fractures occurs in subjects not suffering from DXA-assessed osteoporosis, in recent years, several tools have been developed to predict the future risk of fracture in postmenopausal women, mainly based on clinical risk factors. Currently, the most used tool is FRAX®. However, in Italy has been developed a new algorithm derived fracture risk assessment (DeFRA®) to introduce graduated dichotomous variables to correct limitations FRAX® and previous fragility fractures at more different skeletal sites and more other secondary osteoporosis.However, this algorithm shows some limitations in its application to primary care: first of all the difficulty to access to this tool by GPs in daily practice. Objectives: To verify the usefulness of a simple method that does not require a commitment from GPs to screen patients at risk of fractures to be addressed to bone metabolism specialized clinical centers. Methods: As part of the clinical audit organized by ERGO (Emilia-Romagna Osteoporosis Group), the project aimed to evaluate the approach to osteoporosis by a group of medical doctors from different specialties through the use of a self-administered paper questionnaire, including all the data necessary to complete FRAX® and DeFRA® algorithms to all patients presenting to outpatient service. Inclusion criteria for the screening of osteoporosis were according to 2012 NICE guidelines (1). Thus, 649 patients (537 women and 112 men) were included. Results: Previous fragility fractures history was reported in 29% of women and 15% of men: vertebral in 102 (1 in 57 and >1 in 47 subjects); femoral in 21 and, in other skeletal sites, in 86 subjects. Stratification of patients in risk factor group was: no risk 40%, 1 risk 30%, 2 risks 20% and 3, or more, 10%. In the graph1 fracture events in each risk group are reported. The % of fractures appears to be related to the number of risk factors and the increase parallels to the number of risk factors. It is important to note that the other fractures (in addition to vertebrae and femur) are closely related to risk factors. The incidence of fractures was not related to age because the average age of those with three or more risk factors was 68±10, less than the average age of those who have no risk factors 74±6, p value <0.0001. Only about 40% of patients with previous fragility fractures had a DXA-assessed diagnosis compatible with osteoporosis (T score <-2.5 SD). Effectively, independently from DXA score, the questionnaire filled by the patient may be able to adequately discriminate the risk of fracture. Conclusions: The identification of patients at risk through the simple compilation of an appropriate questionnaire allows the GP to address subjects to a bone metabolism specialized clinical center for a better diagnostic definition and adequate therapeutic decisions on cost-effectiveness basis. References: Osteoporosis: assessing the risk of fragility fracture. Guidance.nice.org.uk/cg146, 2012. Disclosure of Interest: None declared